Representasi Profesi Wartawan Dalam Lagu “Kisah Seorang Wartawan” Karya Jamal Abdillah - Zannuba Chavilla Andjari; M Amin Sihabudin; Ahmad Harun Yahya (ScidacPlus, 2024)
The journalist profession has an important role in the process of delivering messages to the wider community. Representation of this profession is not only limited to writing, it can also be found in a song work. The Story of a Journalist is a song composed by Jamal Abdillah that describes the experiences and challenges faced by a journalist. This study aims to clarify how the representation of the journalist profession and the content of the message in the song